(untitled) (Journal of Forest and Natural Resource Management, 2025)
Understanding how sympatric large carnivores coexist through resource partitioning is critical for their conservation in human-influenced landscapes where prey availability and human pressures fluctuate. This study examined and compared the dietary composition, prey selection, and dietary overlap of Royal Bengal tigers (Panthera tigris tigris) and common leopards (Panthera pardus) in two low-land protected areas of Nepal. The study draws from the analysis of prey remain identified in the 141 and 122 scats sample of tiger and leopard respectively collected between 2013 and 2015. Dietary overlap between the two predators was calculated using Pianka’s niche overlap index. A total of 15 prey species including domestic animals were identified revealing a broader prey size range of tiger compared to leopard. While selective predation proffering larger herbivores was found in Chitwan, it was appeared more opportunistic patterns in Parsa. Dietary niche overlap between two predator was low to moderate (Pianka’s index 0.22– 0.23), indicating that size-based prey partitioning and selective predation reduced direct competition and facilitate coexistence The study finding highlights the importance of maintaining diverse and abundant wild prey populations across all body-size classes to support the long-term coexistence and conservation of tigers and leopards in Nepal’s Terai region.